Growing Apart: A Longitudinal Assessment of the Relation Between Post-traumatic Growth and Loneliness Among Combat Veterans - Stein, Jacob Y.; Levin, Yafit; Bachem, Rahel; Solomon, Zahava (Frontiers in Psychology, 2018)
The aftermath of war-related trauma may entail psychological devastation and is typically accompanied by various deleterious phenomena. These include, but are not limited to, high rates of loneliness. However, trauma may also result in positive outcomes such as personal, spiritual, and relational prosperity, which are typically considered under the conceptual framework of post-traumatic growth (PTG). PTG may theoretically contribute to either loneliness amelioration (e.g., via increasing one’s appreciation of close relationships) or exacerbation (e.g., by increasing one’s sense of undergoing experiences that others do not share). Loneliness, on the other hand, may potentially hinder PTG by fostering negative social cognitions and behaviors, or otherwise lead to personal growth. The relations between the two phenomena, however, have yet to be investigated. Filling this gap, the current study examined the aforementioned potentialities by utilizing an autoregressive cross-lagged modeling strategy (ARCL) with a cohort of 260 Israeli combat veterans assessed 30, 35, and 42 years after their participation in the 1973 Yom Kippur War. Results indicated that higher rates of PTG were consistently related to higher rates of loneliness both cross-sectionally and longitudinally. Loneliness, however, did not longitudinally predict PTG rates. It is suggested that these findings may be understood in light of the observation that veterans’ loneliness is primarily related to the experience of being experientially out of sync with people who have not endured war experiences. It is suggested that this experiential loneliness may include not only the negative but also the positive ramifications of undergoing such traumas (i.e., PTG). We, therefore, argue that while PTG may include authentic positive transformations it may also lead to more negative ramifications, and these should be identified and addressed by researchers and clinicians alike. Thus, as study limitations are acknowledged, clinical implications, and future research directions are suggested.